2004
DOI: 10.29310/wp.2003.17
|View full text |Cite
|
Sign up to set email alerts
|

Migration and the Environment in the Galapagos: An analysis of economic and policy incentives driving migration, potential impacts from migration control, and potential policies to reduce migration pressure

Abstract: From 1974 through 1997 the Galapagos experienced very rapid population growth, around six per cent per year. Sustained at this level, the population would continue to double every 12 years. Increased population brings an increased risk of invasive introduced species, which endangers the fragile ecosystems. On 18 March 1998, a Special Law was passed to protect the Galapagos. This law severely limits migration to the islands. We discuss the environmental problems that motivated the law, describe the law, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Tourism is the main engine driving the Galapagos economy. In 2004, it was reported that tourism employs 40% of the residents and represents almost 65% of the local economy (Kerr et al 2004). In 2016, Pizzitutti et al estimated that nearly 60% of residents are associated with tourism and that tourism accounts for nearly 80% of the local economy.…”
Section: Galapagos Economic and Social Changesmentioning
confidence: 99%
“…Tourism is the main engine driving the Galapagos economy. In 2004, it was reported that tourism employs 40% of the residents and represents almost 65% of the local economy (Kerr et al 2004). In 2016, Pizzitutti et al estimated that nearly 60% of residents are associated with tourism and that tourism accounts for nearly 80% of the local economy.…”
Section: Galapagos Economic and Social Changesmentioning
confidence: 99%
“…This influx of migrants and visitors in recent years has been accompanied by many introduced plants and animals (Mauchamp 1997; Kerr et al 2004; Watkins and Cruz 2007), some of which have become invasive and not only threaten endemic species, but also affect the local human population through changes in land use and shifts in livelihoods. The problem has become so widespread in the archipelago that introduced plants have been deemed one of the greatest threats to the terrestrial ecosystem of the islands (Kerr et al 2004).…”
Section: Study Areamentioning
confidence: 99%
“…Thousands of new residents began to migrate from the mainland of Ecuador, attracted by the promise of lucrative opportunities linked to the islands' rich marine and terrestrial ecosystems and the lack of economic opportunities in many parts of the mainland (Borja 2003;Kerr, Cardenas, and Hendy 2004). The fast-paced development of the tourism industry contributed to the growth of the local population, from under 10,000 in 1990 to nearly 23,000 residents today (Instituto Nacionál de Estadistica y Censos 2010).…”
Section: Introductionmentioning
confidence: 99%